Questionnaire Survey on Vaccination Willingness and the Status of COVID-19 Vaccination Among Patients with Rheumatic Disease: A Single-Center Survey in China - Wang F (Patient Preference and Adherence, 2022)
Feng Wang Rheumatology and Immunology Department, Heping Hospital Affiliated to Changzhi Medical College, Changzhi, 046000, People’s Republic of ChinaCorrespondence: Feng Wang, Department of Rheumatology and Immunology, Heping Hospital Affiliated to Changzhi Medical College, No. 110, Yan ‘an Nan Lu, Changzhi City, Shanxi Province, 046000, People’s Republic of China, Tel +0086-355-3128612, Email wangfengwf10@163.comIntroduction: The COVID-19 pandemic is an ongoing global pandemic. Patients with rheumatic disease are more likely to be infected with COVID-19 than the general population, and they should be vaccinated against COVID-19 for protection. This study aimed to understand the willingness to receive the COVID-19 vaccine among these patients.Methodology: Patients who came to the Rheumatology and Immunology Department of our hospital from July 3– 20, 2021, were randomly selected for a self-designed survey via an online questionnaire platform. Four hundred seventeen questionnaires were validated.Results: Males were more likely to underestimate the risk of COVID-19 infection than females, and medical workers had a higher perception of COVID-19 infection risk than nonmedical workers (both P < 0.05). Among the included patients, 149 (35.73%) patients were hesitant to be vaccinated, while 268 (64.27%) patients are willing to accept vaccination. Logistic regression analysis showed that men were more willing to be vaccinated than women, and nonmedical workers were more willing to be vaccinated than medical workers (both P < 0.05). A total of 55.40% of the patients did not receive the COVID-19 vaccine. The incidence of adverse reactions for the 167 patients who received the COVID-19 vaccine was 8.98%.Conclusion: The vaccination rate of the patients with rheumatic disease was relatively low, as was their vaccination willingness. Patient sex, whether the patient was a medical worker, and the patient’s level of knowledge about the risk of COVID-19 infection and the impact of vaccination on the disease were key factors.Keywords: COVID-19 vaccine, COVID-19, rheumatic disease, vaccination willingness